FLUKTUASI KELIMPAHAN DAN KERAGAMAN KUPU-KUPU (PAPILIONOIDEA) DI HUTAN KOTA ARBORETUM CIBUBUR JAKARTA - Hasni Ruslan; Christian Flo Ryan; Danang Musyafa; Dimas Mulya (Jurnal Natural, 2022)
The Arboretum City Forest is located in Cibubur, East Jakarta, in this area there is biodiversity, one of which is butterflies. Butterflies act as an indicator of environmental change, in a habitat. There are two types of habitats in this urban forest, open and closed habitats, which greatly affect the diversity of butterflies. This study aims to determine the diversity of butterflies in the two habitats. The research was conducted in May 2021. The method used was a quantitative descriptive method, and the plot was carried out by purposive sampling. The study was carried out 4 times in each habitat (3 plots), with an interval of 1 week of observation. The research was conducted from 08:30 to 12:30, using insect nets and digital cameras. The number of butterflies found in open habitats was more (39 species, 177 individuals) than in closed habitats (25 species. 94 individuals). Based on, and the diversity of butterflies found shows a significant correlation with habitat conditions. In open forest habitats it is more suitable for butterflies. This difference is strongly influenced by the environmental conditions of the habitat, especially light, and plant diversity.